Patient led PROMs must take centre stage in cancer research - Roger Wilson (Research Involvement and Engagement, 2018)
Plain English summary Patient involvement in research is about adding value rather than commenting on technical quality. After 15 years as an involved patient in cancer research I started looking around and I found I was asking myself, where is the next leap in real patient benefit going to come from? Science is making a difference to a few patients with metastatic disease but it has been achieved at a high cost. I looked at the evidence from current practices in cancer care and saw that many patients are still dying within days of taking their last chemotherapy. The ethics of current drug adoption practices and the use of new drugs are being questioned socially and politically. Evidence based practice is asking researchers to find the true value of new treatments. I came to the conclusion that quality of life assessment and patient reported outcome measures (PROMs) which capture subjective patient experience are where real and lasting progress can be made. Quality of life in research is about structured assessment. PROMs are built around the patient experience. Patient involvement is essential. The idea that you can have Patient Reported Outcomes without patient provided inputs to inform the methods and processes used, is irrational and probably unethical. In research there is a lot of scattered activity but no coherent vision for all this work. I propose a vision based on defining patient pathways informed by PROMs. Pathways would underpin a life quality description which patients can easily identify and which doctors would find easy to communicate. Pathways would also offer value to regulators and commissioners by focusing on how clinical activity delivers patient benefit. Abstract Patient involvement is about adding value through the application of experience and the ability to stand back and take a view, rather than commenting on technical quality. After 15 years as an involved patient in cancer research I realized that I was in the position of taking an informed view of the realities of cancer research. When I started looking around I found I was asking myself, where is the next large leap in real patient benefit going to come from? I came to the conclusion that PROs, patient reported outcomes, are where real and lasting progress can be made. I considered current research activity and I am full of admiration for the ingenuity and scientific quality of what is being done. It is making a difference to a few of those with metastatic disease and a few more earlier in their disease experience, but it has been achieved at a high cost both financially and in terms of patient burden. I looked at the evidence from current practices in cancer care and saw that many patients are still dying within days of taking their last chemotherapy, it seems partly because of unrealistic expectations. The ethics of current drug adoption practices and the use of new drugs is being questioned socially and politically raising the challenge of finding the relative value of new treatments in terms of cost and benefit. Regulatory and HTA bodies address this through public and patient involvement but translation of subjective experience into an objectively determined judgment is imperfect. Quality of life and PROs stood out as a critical development area. In research there is no coherent vision but a lot of scattered activity, albeit with active consensus groups among academic researchers. Patient involvement in this area of research needs to develop further and become more effective. The idea that you can have Patient Reported Outcomes without patient provided inputs to inform the methods and processes used, is irrational and probably unethical. I propose that a vision based on defining patient pathways informed by PROs which patients have been involved in developing would underpin a life quality description which patients can easily relate to and which doctors would find easy to communicate. Pathways would also offer value to regulators and commissioners by giving them a focus on how clinical activity delivers patient benefit.